Abnormal Cervical Vestibular-Evoked Myogenic Potentials Predict Evolution of Isolated Recurrent Vertigo into Meniere’s Disease - Lee, Sun-Uk; Kim, Hyo-Jung; Choi, Jeong-Yoon; Koo, Ja-Won; Kim, Ji-Soo (Frontiers in Neurology, 2017)
Introduction: Vestibular-evoked myogenic potentials (VEMPs) can be abnormal in patients with idiopathic recurrent spontaneous vertigo. We aimed to determine whether abnormal cervical vestibular-evoked myogenic potentials (cVEMPs) can predict evolution of isolated recurrent vertigo into Meniere’s disease (MD). Methods: We had followed up 146 patients with isolated recurrent vertigo and an evaluation of cVEMPs for 0 142 months [median=6, interquartile range (IQR)= 0–29] at the Dizziness Clinic of Seoul National University Bundang Hospital from June 2003 to May 2014. We defined the variables associated with a progression into MD and calculated cumulative progression rates. Results: Among the 94 patients with recurrent vertigo and abnormal cVEMPs, 18 (18/94, 19%) showed an evolution into MD while only two of the 50 (4%) patients with normal cVEMPs evolved into MD during the follow-up (p=0.01). The interval between onset of vertigo and development of cochlear symptoms ranged from one month to 13.6 years (median = 3 years, IQR=0.5–4.5 years). Overall, pure-tone audiometry (PTA) threshold at 0.25 kHz [hazard ratio (HR)=1.1, 95% confidence interval (CI)= 1.0–1.2] and abnormalities of cVEMPs (HR=5.6, 95% CI= 1.3–25.5) were found to be significantly associated with a later conversion into MD. The cumulative progression rate was 12% (95% CI = 5–18) at one year, 18% (8–26) at two years, and 22% (11–32) at three years. Conclusion: Abnormal cVEMPs may be an indicator for evolution of isolated recurrent vertigo into MD. Patients with isolated recurrent vertigo may be better managed conforming to MD when cVEMPs are abnormal.